Ontogeny of some species of genus Ipomoea L. in conditions of Forest-Steppe of Ukraine with the different methods of cultivation - L.L. Pavlenko; S.P. Mashkovska (Інтродукція Рослин, 2014)
The ontogenesis of four species of the genus Ipomoea L. (I. purpurea (L.) Roth., I. hederacea (L.) Jacq., I. indica (Burm.) Mevvill. and I. tricolor Cav.) is described. Biomorphological characteristic, diagnostic features and drawings of age states ontogenesis species of the genus Ipomoea data about the duration of the different ways of growing plants, recommendations regarding the method of growing species in conditions of Forest-Steppe of Ukraine are given.